(3GdJfejI GdGbJUGOjI h GdGLJeGYjI h GdJZjjQ Gdgjcdj aj GdOhd GdYQHjI (B:s (3GdefgL , GdfXQjI , GdbjGS (B/s - (3efOhQ, YUGe YeQs ((3GdGScfOQjI(B: s (3OGQ GdcJH GdeUQjI(B, s, 2011)
(3eaghe h fXQjGJ GdJfejI GdGbJUGOjI h GdJZjjQ GdJcfhdhLj aj GdOhd GdYQHjI , eaghe h eMOOGJ Gdgjcd GdGbJUGOj h eXGgQ GJZjjQ Gdgjcdj , GdSjGSI GdgjcdHI h fXQjGJ h eOGNd bjGS GdJZjjQ Gdgjcdj , bjGS GdYdGbI GdeJHGOdI Hjf GdJZjjQ Gdgjcdj h YedjI GdJfejI GdGLJeGYjI h GdGbJUGOjI aj GdOhd GdYQHjI h eUQ h JMdjd GJLGYGJ GdJZjjQ Gdgjcdj aj GdfTGW GdGbJUGOj GdeUQj , h CNjQG bjGS gPG GdJajjQ h JMOjO CSHGHgs
(3eQGLY U(B.307 (3; edMb GMUGFj U(B.325 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdJfejIs; (3GdJfejI GdEbJUGOjI hGdGLJeGYjIs; (3GdJfejI(B- (3GdhWf GdYQHjs